Determinants and Regulations of Discretionary in Administrative Decisions And the Role of the Judiciary in Monitoring Them - Al-Eissa , Ghzayel (The Arab Journal of Administration, 2019)
This research aims to define the determines and regulations of the discretionary authority of the administration, and the role of the judiciary in its control. This has been divided into four sections: the first of which consternated on the concept of discretionary power, and the difference between it and the restricted power. The second section addressed the justifications of the existence of the discretion with the management activity. The third section was the relation between areas of discretion and the administrative decisions. While the fourth section deal with the elements of using the discretion in the administration work. Citing some cases from the Saudi Board of grievances as representing the judicial oversight in Kingdom of Saudi Arabia. The research ended with a number of results as follow: It is difficult to regulate the administration in details with the roles of law in the light of the variety and diversity of administrative situations, positions and their continuous change in accordance with what surround the work of changes and developments with the internal or external work environment. Therefore, the regulator will not be right if he tries to face all the situations in advance, yet he shall delegate to the administration the ability to interfere in certain circumstances insuring the stability of work in the government sectors. It has two types of authorities, which are restricted and discretionary. The discretionary power of the administration is legal authority. When the administration starts its discretion to practice the law, it does not derive this power from itself but derive it from the flexible a legal rule that it applies. The discretionary power does not mean absolute power, but the administrative judiciary has defined its areas and regulates its rules, which are supposed to not exceed them in such a way to ensure that they are used within the scope of legality and public interest with specific controls that ensuring the authority is not abused by the administrative organization. The authority, whether restricted or discretionary, is only a method to apply the law, and therefore judicial control of the administration is inevitable in the exercise of power, whether restricted or discretionary.